Laboratory and field experiment validations on the use of hydraulic transients for estimating buried water pipeline deterioration. (March 2023) - Alexander, Jane; Li, Zhao; Lee, Pedro; Roxburgh, Colin; Davidson, Mark
This paper investigates the validity of using fluid transients as a rapid screening tool to augment existing methods for assessing the condition of buried water systems. In particular, the paper provides one of the first detailed investigations on the impact of pipe wall deterioration on the characteristic of transient waves in both laboratory and field experiments. Laboratory pipeline sections were deteriorated by an accelerated corrosion process using controlled electrolytic cell reactions, and three cases were considered: where corrosion is limited to the internal wall, limited to the external wall, and where both internal and external walls are corroded. Hydraulic transient tests were carried out to measure the transient wave speed in these corroded pipe sections, and the measurements are found to be consistent with the theoretical predictions using the observed wall thickness loss, confirming that wave speed can be used as an indicator of pipe wall deterioration. Field experiments were carried out in the water supply network in the Waimakariri District, New Zealand, to validate the performance of this pipe condition diagnostic methodology. Transient tests were conducted on selected 60-year-old sections of asbestos cement (AC) pipelines and sensors were connected to standard fire hydrants to measure the wave speeds and wave reflections. Compared with the theoretical calculated wave speed of intact pipelines, a 140–300 m/s wave speed decrease was observed in most of the tested sections which is in line with the expectation for pipelines of this age. The wave speeds were used to predict the in-situ thickness of the pipe wall and these predictions were found to match with computed tomography X-ray scan results of the excavated pipe with good accuracy. The same methodology was also used to correctly detect an unrecorded plastic pipe section in the AC pipe network.